2011
DOI: 10.1002/dneu.20865
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Bmp7 levels are required for the differentiation of midline guidepost cells involved in corpus callosum formation

Abstract: Guidepost cells are essential structures for the establishment of major axonal tracts. How these structures are specified and acquire their axon guidance properties is still poorly understood. Here, we show that in mouse embryos appropriate levels of Bone Morphogenetic Protein 7 (Bmp7), a member of the TGF-β superfamily of secreted proteins, are required for the correct development of the glial wedge, the indusium griseum, and the subcallosal sling, three groups of cells that act as guidepost cells for growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
(85 reference statements)
2
9
0
Order By: Relevance
“…Contribution of the TGF signaling to the differentiation of the midline glia was also reported in the recent literature [125]. Sánchez-Camacho and collaborators observed an expression of BMP7 in the presumptive tissue of the midline glia and found that the genetic loss of BMP7 in mice results in profound alterations of the glial wedge and the indusium griseum glia.…”
Section: Role Of Guidepost Cells In the Formation Of The Corpussupporting
confidence: 55%
“…Contribution of the TGF signaling to the differentiation of the midline glia was also reported in the recent literature [125]. Sánchez-Camacho and collaborators observed an expression of BMP7 in the presumptive tissue of the midline glia and found that the genetic loss of BMP7 in mice results in profound alterations of the glial wedge and the indusium griseum glia.…”
Section: Role Of Guidepost Cells In the Formation Of The Corpussupporting
confidence: 55%
“…Various mutant mice that lack proteins involved in either axon guidance and/or midline guidepost cell development have been previously identified with callosal agenesis (Bagri et al, 2002; Fothergill et al, 2014; Islam et al, 2009; Keeble et al, 2006; Magnani et al, 2014; Mendes et al, 2006; Niquille et al, 2009; Piper et al, 2009b; Sanchez-Camacho et al, 2011; Smith et al, 2006). The prevailing hypothesis from these studies has therefore been that congenital callosal agenesis predominantly results from defects in axon guidance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Midline crossing of callosal axons is controlled by several glial and neuronal guideposts specifically located along the callosal path. BMP-7 has been shown to be required at different steps of organization and differentiation of these guidepost cells, which allows formation of the corpus callosum (Sanchez-Camacho et al, 2011). Additional evidence also indicates that BMP-7, secreted from the meninges, is involved in a morphogenic cascade, including Wnt3a and GDF-5, allowing correct corpus callosum development and prevents premature axon projection (Choe et al, 2012).…”
Section: Bmps In Nervous System Development and Maintenancementioning
confidence: 99%